Smart Gas Sensors: Recent Developments and Future Prospective - Zong, Boyang; Wu, Shufang; Yang, Yuehong; Li, Qiuju; Tao, Tian; Mao, Shun (Nano-Micro Letters, 2024)
Gas sensor is an indispensable part of modern society with wide applications in environmental monitoring, healthcare, food industry, public safety, etc. With the development of sensor technology, wireless communication, smart monitoring terminal, cloud storage/computing technology, and artificial intelligence, smart gas sensors represent the future of gas sensing due to their merits of real-time multifunctional monitoring, early warning function, and intelligent and automated feature. Various electronic and optoelectronic gas sensors have been developed for high-performance smart gas analysis. With the development of smart terminals and the maturity of integrated technology, flexible and wearable gas sensors play an increasing role in gas analysis. This review highlights recent advances of smart gas sensors in diverse applications. The structural components and fundamental principles of electronic and optoelectronic gas sensors are described, and flexible and wearable gas sensor devices are highlighted. Moreover, sensor array with artificial intelligence algorithms and smart gas sensors in “Internet of Things” paradigm are introduced. Finally, the challenges and perspectives of smart gas sensors are discussed regarding the future need of gas sensors for smart city and healthy living. Highlights: 1 Recent developments of advanced electronic and optoelectronic gas sensors are introduced. 2 Sensor array with artificial intelligence algorithms and smart gas sensors in “Internet of Things” paradigm are highlighted. 3 Applications of smart gas sensors in environmental monitoring, medical and healthcare applications, food quality control, and public safety are described.